We Don't Become Refugees by Choice - Meade, Teresa A. author. aut Link
XXIII, 270 p. 33 illus.
Keywords: “A riveting biography of an unstoppable woman that takes us from Warsaw through Italy to settle in California, where she was a Sanctuary activist until her death at 93.” —Linda Gordon, Florence Kelley Professor of History, New York University, USA “Meade vividly weaves together the personal and the political, and memory and history, in this gripping page-turner about Mia Truskier’s remarkable life and the global twentieth century.” —Aviva Chomsky, Salem State University, USA "One of the joys of first-person testimony is the uncovering of the many layers of history and the historical narrative. Meade's conversations with Mia Truskier reveal the complexity of individual identity within a larger group. This is a life story drawn from testimony and the voice of the past -- thoughtful and imaginative." —Ronald J. Grele, Former Director, Columbia University Oral History Research Office, US This book traces the life ofMaria Mia Truskier, who fled the Nazis as a young Polish Jew in early 1940 and once safely resettled in the United States, became an activist for other refugees, earning renown in the Bay Area as “the oldest refugee” of the East Bay Sanctuary Covenant. Mia worked for decades assisting those fleeing from war, violence and hardship, mainly from Central America and Haiti. Based on extensive interviews with Truskier before she passed away, as well as memorabilia from her own lifetime, including coded letters, newspaper clippings, and old photographs, this book results in a complex and multi-layered oral history. As Mia drew on memories of her life in Europe and World War II, she was situating and constructing those memories while re-reading and discovering these artifacts alongside the author of this book, and ultimately relating the ways that she and her family years later sought to make a difference for other refugees, drawing a connection between two major eras of human displacement: the end of World War II and today. Teresa Meade is the Florence B. Sherwood Professor of History and Culture at Union College in Schenectady, NY, USA.